Growth of Rice (Oryza sativa) Varieties: Mendawak, Inpari 34, Ciherang, and Bangir in Ciganjeng Village, Pangandaran District - Muhamad Khais Prayoga; Neni Rostini; Tualar Simarmata; Mieke Rochimi Setiawati; Silke Stoeber; Kustiwa Adinata (Jurnal Biodjati, 2018)
Type of rice varieties is one of the important factors that affecting rice production. For countries, rice breeders of Indonesia can take advantage of specific environmental potential in determining the distribution policy of superior varieties. The purpose of this study was to observe the appearance of plant height and the number of tillers of four rice varieties in Ciganjeng Village, namely Mendawak, Inpari 34, Ciherang, and Bangir. The design used completely randomized block design and repeated three times. Observations were carried out eight times in the vegetative phase, started from 14 days to 63 days after planting. This research was participatory and involved farmers. Farmers roled as observers to measure and record observation. All data analyzed by ANOVA with tukey’s HSD test as post hoc test. The results showed that both Inpari 34 and Bangir variety had the highest average plant height growth while Mendawak and Bangir has the highest average number of tillers.